The Analysis of Cell Cycle–related Proteins in Ovarian Clear Cell Carcinoma Versus High-grade Serous Carcinoma. (November 2018) - Hazama, Yukiko; Moriya, Takuya; Sugihara, Mika; Sano, Rikiya; Shiota, Mitsuru; Nakamura, Takafumi; Shimoya, Koichiro
Abstract : In Japan, the frequency of ovarian clear cell carcinoma (CCC) is twice as high as that in the United States and Europe. Often, patient prognosis with CCC is poor because of chemoresistance. Here, we focus on the cell cycle, which is one of the mechanisms of chemoresistance. To detect the informative markers and improve the strategy of chemotherapy for CCC, we performed immunohistochemical staining of cell cycle–related proteins in ovarian malignant tumors. We detected that each of the 29 samples of CCC and high-grade serous carcinoma (HGSC) were necessary to reveal the significant differences in immunostaining and prognosis. We performed the immunostaining analysis using the antibodies of cell cycle–related proteins such as Ki-67, Cdt1, MCM7, and geminin. The positive rate of Cdt1 in the CCC group was significantly higher than that in the HGSC group ( P <0.0001). However, the positive rate of geminin in the HGSC group was significantly higher than that in the CCC group ( P <0.0001). The overall survival of CCC patients with high labeling index of Cdt1 was significantly worse than that of CCC patients with low labeling index of Cdt1 ( P= 0.004). The study results suggested that the cancer cells of CCC and HGSC exist in the G1 phase and S, G2, and M phases, respectively. The differences in cell cycle of CCC might be one of the reasons for chemotherapy resistance. Further investigations are necessary to reveal the usefulness of Cdt1 as a biomarker in CCC.